Britain's Health Services (London : Communist Party of Great Britain)
1942-10 1942 1940s 40 pages UNIFORM. — Cost of providing and making-up uniform to be borne by the employing institution or cash payments made in lieu. RESTRICTIONS ON INDIVIDUAL LIBERTY. Petty restrictions (amounting in some cases to a form of tyranny) and limitations on the liberty of nurses when off-duty to be stopped forthwith. The Nurses Home should be run as a hostel under a warden, who is not a trained nurse, with an elected Committee of the residents to decide questions of regulations, recreations, etc. MARRIAGE.— No form of restraint, direct or indirect, should be brought to bear on any nurse, qualified or student, who wishes to marry and remain in the hospital's service. TRADE UNIONS.— Nurses should feel completely free to join Trade Unions which exist to protect their rights and advance their claims for betterment of salaries and conditions. Any form of victimisation on the part of the matron or hospital management should be exposed and met with the strongest possible action by the organised Labour movement. Instances of suspected victimisation should always be communicated to the Secretary of the Trades Council, which exists in every city and town, or to the local Communist Party. iii. General.— To meet the grave shortage of trained staff the Communist Party calls for immediate steps to be taken to shorten the period of training for nurses. In Industry (where there are many skilled and professional workers) it has been found possible without detriment to the quality of work to "telescope" the usual courses of apprenticeship and training. The General Medical Council are allowing medical students to take their final examinations three months earlier than usual and there is no reason why, with a "rationalisation" of the training processes, a reduction of, say, six months should not be effected in the training period for nurses. At the same time an alternative system of examination and training should be established to regularise the position of the many thousands of girls who have failed to reach the comparatively high standards at present required by the State examinations, but who are nevertheless quite competent for much routine nursing and ordinary duties. The State Register should be extended to provide for this alternative grade, who might be classified as "Registered Ancillary Nurses" (R.A.N's). R.A.N's would not be allowed to practise except under the supervision of a State Registered Nurse, and salaries would be at a lower level than for fully qualified nurses. All "Assistant 22 15X/2/103/252